Abnormal multifocal ERG findings in patients with normal-appearing retinal anatomy - Talamini, Christine L. (Doc Ophthalmol, 2011)
To evaluate eyes with abnormal visual fields and multifocal electroretinograms (mfERGs) but normal-appearing frequency-domain optical coherence tomography (fdOCT) scans, the thicknesses of the outer retinal layers were measured. A total of 25 eyes from 17 patients, including 15 eyes previously tested (Dale et al. in Doc Ophthalmol 120(2):175–186, 2009) were examined. All patients were evaluated with standard automated perimetry (SAP) using the 24-2 and/or 10-2 program (Zeiss Meditec), mfERG with 103 hexagons (Veris, EDI), and fdOCT imaging (3DOCT-2000, Topcon) with scans of the macula. All patients had reliable visual fields showing macular defects and good quality mfERG and fdOCT results. The mfERG results were classified as abnormal based on decreased amplitudes and/or increased latencies corresponding to the abnormal visual field. Based on visual inspection, three experienced observers classified the fdOCT scans as normal or inconclusive, as opposed to clearly abnormal. Retinal layers of the fdOCT scans were manually segmented with the aid of a computer program and compared to mean thicknesses from 20 controls. The thicknesses of the outer segment plus retinal pigment epithelium, total receptor, and inner nuclear layers were measured. Quantitative analysis of fdOCT scans demonstrated thinning of the outer retina in some scans that was not readily apparent on visual inspection. One or more of the outer retinal layers was significantly thinner in 15 of the 25 eyes. The absence of significant thinning in the other 10 eyes represents instances in which functional loss measured by visual fields and mfERGs can precede clear structural changes on fdOCT.